Restoration of degraded lands for carbon stock enhancement and climate change mitigation: the case of Rebu watershed, Woliso Woreda, Southwest Shoa, Ethiopia - Diriba Megersa Soboka; Fantaw Yimer (Journal of Degraded and Mining Lands Management, 2022)
This study was conducted to estimate carbon stock enhancement and climate change mitigation potential of restoration effort in Rebu Watershed, Woliso Woreda, Ethiopia. Two restored lands of thirteen years old were randomly selected from two kebeles. Biomass and soil data were collected systematically from nested plots. Mensuration of woody species, soil, and grass/litter samples was collected from the subplots of the nested plots. A total of 72 composite soil samples were collected. The results showed the positive impact of restoration activity on enhancing biomass and soil organic carbon stocks. The restored land ecosystem had shown higher carbon stock of (138.51 ± 27.34 t/ha) than the adjacent unrestored land ecosystem (101.43 ± 21.25 t/ha), which confirmed the potential of restoration in enhancing the carbon stock and mitigating climate change. Hence, the restored land use type has been stored about 8.37 t/ha of carbon dioxide equivalent (CO2e) in biomasses. The restored land use type has mitigated climate change (absorb CO2) by 7.7 times than the adjacent unrestored land use type in this study. The significant values in restored land use types were due to the enhanced vegetation and land cover, which contributed to the biomass and soil organic carbon accumulation. Moreover, the lower values in unrestored land use type were due to the continuous degradation and disturbance from livestock and human beings. Therefore, the result of this study showed that protecting the degraded lands from any disturbance could enhance the carbon stocks of the ecosystem and mitigate the carbon emission rate.